Vigilance-Avoidance Toward Negative Faces in Social Anxiety With and Without Comorbid Depression - Kishimoto, Tomoko; Wen, Xu; Li, Mingzhu; Zhang, Ru-Yuan; Yao, Nisha; Huang, Yunzhen; Qian, Mingyi (Frontiers in Psychiatry, 2021)
Despite the growing evidence for the attentional bias toward emotional related stimuli in patients with social anxiety disorder (SAD), it remains unclear how the attentional bias manifests in normal individuals with SAD and/or depressive traits. To address this question, we recruited three groups of normal participants with different psychiatric traits—individuals with comorbid SAD and depression (SADd, N = 19), individuals with only SAD (SAD, N = 15), and healthy control individuals (HC, N = 19). In a dot-probe paradigm, participants view angry, disgusted, and sad face stimuli with durations ranging from very brief (i.e., 14ms) that renders stimuli completely intangible, to relatively long (i.e., 2000ms) that guarantees image visibility. We find significant early vigilance (i.e., on brief stimuli) and later avoidance (i.e., on long stimuli) toward angry faces in the SADd group. We also find vigilance toward angry and disgusted faces in the SAD group. To our best knowledge, this is the first study to unify both vigilance and avoidance within the same experimental paradigm, providing direct evidence for the “vigilance-avoidance” theory of comorbid SAD and depression. In sum, these results provide evidence for the potential behavioral differences induced by anxiety-depression comorbidity and a single trait in non-clinical populations, but the lack of a depression-only group cannot reveal the effects of high levels of depression on the results. The limitations are discussed.